Therapeutic Community Modality Program: Experiences of Incarcerated Women in City Jail Female Dormitory - Relatorres, Queen Henyelour S.; Pioquinto, Paulino V. (Future Science / FSH-PH Publications, 2025)
This study aimed to explore the experiences of incarcerated women in female dormitory in Cebu City Jail on Therapeutic Community Modalities Program which specifically delved on the experiences, effects and aspirations of the informants in therapeutic community modality programs. This qualitative phenomenological study used an interview guide to explore the experiences of ten incarcerated mothers in the female dormitory of Cebu City Jail participating in the Therapeutic Community Modalities Program. The Collaizzi approach was applied to analyze the data and identify cluster themes and emergent themes characterizing the studied phenomena. Based on the results and findings of the study, nine (9) emergent themes were identified. For the experiences of the informants on therapeutic community modality program the following themes are formulated namely: Submissive to Routine Positive Behavioral Approach, A Family is Found Inside Prison, Regrets Always Comes in the End and There is No Such Thing as Free. For the effects of therapeutic community modality programs on the lives of the informants the following themes are formulated namely: Positive Behavioral Transformation, Improved Incarcerated Mothers-Child Communication and their Children and Unwavering Faith induce Self-Reliance. For the aspirations of informants the following themes are formulated namely: A Systematize Motherhood Behind Bars Program and Reward System for Every Significant Deed. Therapeutic Community Modality Program indeed serves as fortress of reformation among incarcerated mothers. However, like any other intervention program, it has to be monitored and evaluated for possible improvement so that it can addressed the rehabilitation and reformation needs of incarcerated mothers.